Expression Quantitative Trait Loci (eQTL) Mapping in Korean Patients With Crohn’s Disease and Identification of Potential Causal Genes Through Integration With Disease Associations - Jung, Seulgi; Liu, Wenting; Baek, Jiwon; Moon, Jung Won; Ye, Byong Duk; Lee, Ho-Su; Park, Sang Hyoung; Yang, Suk-Kyun; Han, Buhm; Liu, Jianjun; Song, Kyuyoung (Frontiers in Genetics, 2020)
Background: Expression quantitative trait loci (eQTL) datasets have extensively been used to help interpret genome-wide association study signals. Most eQTL analyses have been conducted with populations of European ancestry. Objective: To determine the most functionally relevant genes at the Crohn’s disease loci identified in genome-wide association studies (GWAS) involving Asian populations and to find novel disease-associated genes, we conducted an eQTL analysis. Methods: eQTL analysis was pefromed using whole-blood RNA-sequencing of 101 Korean patients with Crohn’s disease. FastQTL was used for a pair-wise genome analysis of ~ 6.5 M SNPs and ~ 22 K transcripts. Results: We identified 135,164 cis-eQTL and 3,816 eGenes with a false discovery rate less than 0.05. A significant proportion of the genes identified in our study overlapped with those identified in previous studies. The significantly enriched pathways of these 3,816 eGenes included neutrophil degranulation and small molecule biosynthetic process. Integrated analysis of Crohn’s disease GWAS with Korean eQTL revealed two putative target genes, TNFSF15 and GPR35, at two previously reported loci, whereas TNFSF15 only with the whole blood data from the Genotype-Tissue Expression (GTEx) project, highlighting the utility of building a population-specific data set, even of modest size. The risk alleles of these genes were found to be associated with lower expression levels of TNFSF15 and GPR35, respectively. Our eQTL browser can be accessed at “http://asan.crohneqtl.com/”. Conclusion: This resource would be useful for studies that need to employ genome-wide association analyses involving Asian populations.